2018
DOI: 10.1016/j.heliyon.2018.e00760
|View full text |Cite
|
Sign up to set email alerts
|

Role of genetic factors and ethnicity on the multiplicity of Plasmodium falciparum infection in children with asymptomatic malaria in Yaoundé, Cameroon

Abstract: In this cross-sectional study, we investigated host genetic factors and ethnic variation in circulating Plasmodium falciparum merozoite surface protein 2 (msp-2) clones among children with asymptomatic malaria.Isolates from seventy two asymptomatic malaria children were used for genotyping block 3 of msp-2 gene by nested polymerase chain reaction (PCR). Sickle cell trait and glucose-6-phosphate dehydrogenase (G6PD) deficiency were analysed by restriction fragment length polymorphism of DNA products from PCR ta… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
7
0

Year Published

2019
2019
2022
2022

Publication Types

Select...
4
1

Relationship

1
4

Authors

Journals

citations
Cited by 7 publications
(7 citation statements)
references
References 49 publications
(53 reference statements)
0
7
0
Order By: Relevance
“…For example, studies in Colombia and Cameroon found that there was a high probability of sampling-related parasites in different residents of the same and neighboring households [65,66]. Yet, there are also reports that have identified limited spatiotemporal correlation in parasite strains, consistent with local transmission networks being more stochastic in nature [67,68].…”
Section: Transmission Intensity Amentioning
confidence: 99%
See 1 more Smart Citation
“…For example, studies in Colombia and Cameroon found that there was a high probability of sampling-related parasites in different residents of the same and neighboring households [65,66]. Yet, there are also reports that have identified limited spatiotemporal correlation in parasite strains, consistent with local transmission networks being more stochastic in nature [67,68].…”
Section: Transmission Intensity Amentioning
confidence: 99%
“…It has been suggested that approximately 25% of the variation in individual susceptibility is due to host genetic factors [105,106]. Several genetic factors, including the sickle-cell trait, a-thalassemia, gucose-6-phosphate dehydrogenase deficiency, and having the O blood group, offer protection against infection, clinical symptoms, or severe disease [66,107]. An individual's attractiveness to mosquitoes has also been identified as a heritable trait, with those least attractive protected from malaria and those most attractive being most at risk [98,104].…”
Section: Human Geneticsmentioning
confidence: 99%
“…In contrast, previous studies of the COI in African settings have found both higher average COI values in some regions and, in general, greater variability. For example, in Cameroon large mean COIs between 2.33 to 3.82 have been reported [61][62][63]. Conversely, in Ghana the mean COI has been reported to be between 1.13 and 1.91 in 2012-2013 [64].…”
Section: Discussionmentioning
confidence: 98%
“…In countries with limited resources available for malaria control, identifying host genotypes that are associated with asymptomatic parasite carriage within the population can help in selecting the target population for certain control interventions. The influence of host genetics on malaria has been well studied over the past years; however, these studies mainly determine the influence on symptomatic malaria [ 46 ], with very few studies identifying how host genetics, particularly certain host gene polymorphisms, can influence asymptomatic P. falciparum parasite carriage [ 47 ]. This study was set out to determine whether some host factors that are known to protect people living in malaria-endemic settings from symptomatic malaria predispose them to harbor P. falciparum in asymptomatic infections.…”
Section: Discussionmentioning
confidence: 99%